Costs and Reimbursements for Mental Health Hospitalizations at Children's Hospitals. Issue 12 (1st December 2020) - Herndon, Alison C; Williams, Derek; Hall, Matt; Gay, James C; Browning, Whitney; Kreth, Heather; Plemmons, Greg; Morgan, Kate; Neeley, Maya; Ngo, My‐Linh; Clewner‐Newman, Lisa; Dalton, Evan; et al.
Abstract : The financial impact of the rising number of pediatric mental health hospitalizations is unknown. Therefore, this study assessed costs, reimbursements, and net profits or losses for 111, 705 mental health and non–mental health medical hospitalizations in children's hospitals with use of the Pediatric Health Information System and Revenue Management Program. Average financial margins were calculated as (reimbursement per day) – (cost per day), and they were lowest for mental health hospitalizations ($136/day), next lowest for suicide attempt ($518/day), and highest for other medical hospitalizations ($611/day). For 10 of 17 hospitals, margin per day for mental health hospitalizations was lower than margin per day for other medical hospitalizations. For these 10 hospitals, the total net loss for inpatient and observation status mental health hospitalizations, compared with other medical hospitalizations, was $27 million (median, $2.2 million per hospital). Financial margins were usually lower for mental health vs non–mental health medical hospitalizations. Abstract :